Advances in Delayed-Onset Muscle Soreness (DOMS): Part I: Pathogenesis and Diagnostics - Hotfiel, Thilo; Freiwald, Jürgen; Hoppe, Matthias Wilhelm; Lutter, Christoph; Forst, Raimund; Grim, Casper; Bloch, Wilhelm; Hüttel, Moritz; Heiss, Rafael (Sportverletzung · Sportschaden, 2018)
Delayed-onset muscle soreness (DOMS) is a type of ultrastructural muscle injury. The manifestation of DOMS is caused by eccentric or unfamiliar forms of exercise. Clinical signs include reduced force capacities, increased painful restriction of movement, stiffness, swelling, and dysfunction of adjacent joints. Although DOMS is considered a mild type of injury, it is one of the most common reasons for compromised sportive performance. In the past few decades, many hypotheses have been developed to explain the aetiology of DOMS. Although the exact pathophysiological pathway remains unknown, the primary mechanism is currently considered to be the ultrastructural damage of muscle cells due to unfamiliar sporting activities or eccentric exercise, which leads to further protein degradation, apoptosis and local inflammatory response. The development of clinical symptoms is typically delayed (peak soreness at 48 – 72 h post-exercise) as a result of complex sequences of local and systemic physiological responses. The following narrative review was conducted to present an overview of the current findings regarding the damaging mechanisms as well as the pathophysiology of DOMS and its diagnostic evaluation.
Keywords: muscle damage; muscle injury; muscle strain; exercise-induced muscle damage; EIMD; eccentric training; MRI